Do Entrenched Managers Pay Their Workers More? - Henrik Cronqvist; Fredrik Heyman; Mattias Nilsson; Helena Svaleryd; Jonas Vlachos (The Research Institute of Industrial Economics (IUI), 2005)
Based on a two-million-observation panel dataset that matches public firms with detailed data on their employees, we find that entrenched managers pay their workers more. For example, our estimates show that CEOs with more control rights (votes) than all other blockholders together, pay their workers about 6%, or 2,200 per year, higher wages. Since cash flow rights ownership by the CEO and better corporate governance are found to mitigate such behavior, we interpret the higher pay as evidence of agency problems between shareholders and managers affecting workers pay. The findings do not appear to be driven by endogeneity of managerial ownership and are robust to a series of robustness checks. These results are consistent with an agency model in which entrenched managers pay high wages because they come with private benefits, such as lower-effort wage bargaining and better CEO-employee relations, and suggest more broadly an important link between the corporate governance of large public firms and labor market outcomes.
Keywords: G32; G34; J31; J33; 330; Corporate Governance; Agency Problems; Private Benefits; Matched Employer-Employee Data; Wages; Führungskräfte; Angestellte; Vergütungssystem; Lohnbildung; Corporate Governance; Prinzipal-Agent-Theorie